PEMBANGUNAN E-LEARNING SENI BUDAYA BALI BERBASIS WEB - Dewa Gede Padma Arta Putra; Eddy Muntina Dharma; Komang Tri Werthi (Jurnal Tekinkom (Teknik Informasi dan Komputer), 2022)
Gahita.Com is a web-based e-learning platform, which provides videos for learning Balinese art and culture. The development of a Web-based Balinese Cultural Arts e-Learning information system on Gahita.Com has been successfully completed in accordance with the Team's agreement. Development is carried out using the Scrum Method where the work is organized into a unit called a backlog so that each progress can be easily tracked. Functionality testing carried out using the blackbox testing method on the development of Gahita e-Learning which consists of Login, User Profile, e-Learning Access, Quiz and Certificate can be said to work as expected. Testing is carried out by testers or product owners without knowing the details of the code implementation of the features or functionality being tested, so that the testing phase can be carried out more flexibly without considering the code aspect. The qualitative approach between the author and the resource person resulted in an alarming statement for the future of cultural arts being eroded by globalization which was considered to have a negative impact so that an e-learning information system was built in which there was a digital library which is expected to be useful for the next generation of cultural arts in Bali.